Progressive Law Dialectics: Statesmen’s Role as Constitution Guardians and the Independence of Indonesia's Constitutional Court - Endriyani Lestari; Fitria Damayanti; Uche Nnawulezi (The Digest: Journal of Jurisprudence and Legisprudence, 2024)
This study examines the filling of public offices with special criteria, as outlined in the constitution, which applies specifically to Constitutional Court judges. However, the term "statesman" is not explicitly defined in the criteria. Progressive law, de facto, emphasizes the substantive dimension of justice in the pursuit of upholding the right to justice and democracy. This paper explores the reconstruction of recruitment and external supervision of constitutional judges, focusing on the qualifications of statesmen from a progressive legal perspective. It also discusses the relevance of the progressive legal understanding of statesman qualifications to the independence of the Constitutional Court in Indonesia. The method employed in this research is normative juridical, conducted through literature review. The findings suggest that constitutional decisions and policies should be based on a justice dimension grounded in progressive law. The qualification of a statesman can be assessed through a track record of daily actions and relationships with the broader environment. By applying statesman qualifications to constitutional judges, it signals their capability and compatibility in ensuring the independence of institutions that prioritize justice in state governance and public administration.